1635. Do Persons With Opioid Use Disorder and Injection-Related Infections Really Need Prolonged Hospitalizations to Complete Intravenous Antibiotic Therapy?. (26th November 2018) - Fanucchi, Laura; Walsh, Sharon; Thornton, Alice; Nuzzo, Paul; Lofwall, Michelle
Abstract: Background: Persons with opioid use disorder (OUD) hospitalized with severe, injection-related infections (e.g., endocarditis) often remain inpatient to complete intravenous (IV) antibiotics due to assumptions that, if outpatient, patients will inject drugs into the IV catheter and will fail to complete prescribed antibiotic regimens. No evidence supports these assumptions, and unfortunately, the inpatient stay infrequently includes OUD pharmacotherapy. The aim is to determine whether inpatients with OUD and injection-related infections can be safely discharged to complete antibiotics through a IV catheter in the context of comprehensive outpatient OUD treatment including buprenorphine. Methods: Pilot proof-of-concept, randomized study enrolling hospitalized adults with OUD and severe injection-related infections. Participants are provided inpatient buprenorphine treatment with counseling and randomized (1:1) to usual care (UC) [completing IV antibiotics inpatient] or to early discharge (ED) [completing IV antibiotics outpatient]. Both groups receive 12 weeks of comprehensive OUD treatment with buprenorphine after discharge. Results: Seventy-six patients screened, 20 met eligibility criteria, provided informed consent, and randomized; 10 to UC and 10 to ED. Similar baseline characteristics; 90% in UC with endocarditis and 100% in ED. Length of stay, UC: 45.9 days (SD ±7.8), ED 22.7 (SD ±7.5) ( P < 0.001). Ten in UC and 9 in ED completed recommended IV antibiotics, one in ED group is still receiving antibiotics; ED finished 19.8 days (SD ±11.7) IV antibiotics outpatient. Self-reported illicit opioid use 30 days before hospitalization compared with 12-week outpatient phase decreased in both groups ( P = 0.009); no significant difference between groups ( P = 0.141) (Figure 1). Conclusion: Early results suggest patients with OUD and complex injection-related infections may be safely discharged to complete IV antibiotics via indwelling catheters if comprehensive OUD treatment with buprenorphine is started while inpatient and continued after discharge. Importantly, while prolonged inpatient care is common practice, viewed as protective but extremely costly, these data suggest that comprehensive outpatient care is feasible and may be equi-effective. Disclosures: All authors: No reported disclosures.